Phase transitions in pseudospin- electron model with direct interaction between pseudospins - Stasyuk, I.V.; Havrylyuk, Yu. (Condensed Matter Physics, 1999)
The analysis of thermodynamic properties of the pseudospin-electron model in the case of zero electron transfer with the inclusion of the direct
pseudospin-pseudospin interaction of ferroelectric type is performed. The
equilibrium conditions in the regimes µ = const and n = const are investigated in the mean ﬁeld approximation. It is shown that the interaction with
electrons leads at the ﬁxed µ value to the possibility of the ﬁrst order phase
transition at the change of temperature with a jump-like behaviour of 〈Sz〉.
In the regime n = const there takes place an instability with respect to
phase separation in the wide range of asymmetry parameter h values. Проведено аналіз термодинамічних властивостей псевдоспін-електронної моделі у випадку відсутності електронного переносу з включенням прямої взаємодії між псевдоспінами сегнетоелектричного
типу. У наближенні середнього поля досліджуються умови рівноваги
в режимах µ = const та n = const. Показано, що взаємодія з електронами при фіксованому значенні µ приводить до можливості фазового переходу першого роду при зміні температури зі стрибкоподібною зміною〈Sz〉. У режимі n = const має місце нестабільність щодо
розділення фаз у широкому інтервалі значень параметра асиметрії
h.